Systemic Immune-Inflammation Index Predicts the Clinical Outcome in Patients with mCRPC Treated with Abiraterone - Lolli, Cristian; Caffo, Orazio; Scarpi, Emanuela; Aieta, Michele; Conteduca, Vincenza; Maines, Francesca; Bianchi, Emanuela; Massari, Francesco; Veccia, Antonello; Chiuri, Vincenzo E.; Facchini, Gaetano; De Giorgi, Ugo (Frontiers in Pharmacology, 2016)
Background: A systemic immune-inflammation index (SII) based on neutrophil (N), lymphocyte (L), and platelet (P) counts has shown a prognostic impact in several solid tumors. The aim of this study is to evaluate the prognostic role of SII in metastatic castration-resistant prostate cancer (mCRPC) patients treated with abiraterone post docetaxel. Patients and Methods: We retrospectively reviewed consecutive mCRPC patients treated with abiraterone after docetaxel in our Institutions. X-tile 3.6.1 software, cut-off values of SII, neutrophil-to-lymphocyte ratio (NLR) defined as N/L and platelets-to-lymphocyte ratio (PLR) as P/L. Overall survival (OS) and their 95% Confidence Intervals (95% CI) was estimated by the Kaplan-Meier method and compared with the log-rank test. The impact of SII, PLR, and NLR on overall survival (OS) was evaluated by Cox regression analyses and on prostate-specific antigen (PSA) response rates were evaluated by binary logistic regression. Results: A total of 230 mCRPC patients treated abiraterone were included. SII ≥ 535, NLR ≥ 3 and PLR ≥ 210 were considered as elevated levels (high risk groups. The median OS was 17.3 months, 21.8 months in SII < 535 group and 14.7 months in SII ≥ 535 (p < 0.0001). At univariate analysis Eastern Cooperative Oncology Group (ECOG) performance status, previous enzalutamide, visceral metastases, SII, NLR, and PLR predicted OS. In multivariate analysis, ECOG performance status, previous enzalutamide, visceral metastases, SII, and NLR remained significant predictors of OS [hazard ratio (HR) = 5.08, p < 0.0001; HR = 2.12, p = 0.009, HR = 1.77, 95% p = 0.012; HR = 1.80, p = 0.002; and HR = 1.90, p = 0.001, respectively], whereas, PLR showed a borderline ability only (HR = 1.41, p = 0.068). Conclusion: SII and NLR might represent an early and easy prognostic marker in mCRPC patients treated with abiraterone. Further studies are needed to better define their impact and role in these patients.